Gaze-contingent multi-resolutional displays: An integrative review - Reingold, Eyal M.; Loschky, Lester C.; McConkie, George W.; Stampe, David M. (My University, 2003)
Gaze-contingent multi-resolutional displays (GCMRDs) place high-resolution information only in the area to which the user’s gaze is directed. This portion of the display is referred to as the area of interest (AOI). Image resolution and details outside the AOI are reduced, lowering the requirements for processing resources and transmission bandwidth in demanding display and imaging applications. This review provides an integrative survey of the current literature on GCMRDs across a wide range of applications. It also provides a general framework within which such research can be integrated, evaluated, and guided. Within this framework, a GCMRD (or “moving window”) is analyzed in terms of (1) its multi-resolutional images (also called “variable-resolution”, “space-variant”, or “level of detail”), and (2) its gaze-contingent (or “foveated” or “eye-slaved”), movement of the AOI. We also synthesize the known human factors research on GCMRDs, and point out important questions for future research and development. Actual or potential applications of this research include flight, medical and driving simulators, virtual reality, remote piloting and teleoperation, infrared and indirect vision, image transmission and image retrieval, telemedicine, video teleconferencing, robotics and artificial vision systems.
Keywords: Eye movements; Saccades; Fixations; Gaze-contingent multi-resolutional displays; Gaze-contingent displays; Area of interest